SUPPLEMENTARY TO THE COMPOSITION OF THE URAL BERYLS AND INCLUSIONS OF SYNGENETIC MINERALS IN THEM - V.I. Popova; V.A. Popov; M.A. Rassomakhin (Минералогия)
In addition to the data of predecessors, the chemical composition of zoned or zoned-sectorial beryl crystals from pegmatites of the Mariinsky and Kvartalny deposits of the Urals emerald mines in the Central Urals, granitic pegmatite of mine no. 242 of the Ilmeny State Reserve and Svetlinsky pegmatite quarry in the South Urals is characterized using scanning electron microscopy and energy-dispersive analysis. The light peripheral zones of prism and pinacoid in crystal sections differ in variations in Al, Fe and Mg contents from the inner zones or areas. The presence of fractures and regenerated fragments of early beryl indicates synmineralization tectonics. In beryl from the Mariinsky deposit, the previously unknown syntactic ingrowths of bavenite and zones of parallel columnar aggregates of co-crystallization of beryl and bavenite, as well as late pyrite, fluorite, gismondine-Ca and tobermorite, are identified. Beryls from mine no. 242 of the Ilmeny State Reserve are yellowish-greenish and bluish with a peripheral white zone and syntactic microingrowths of annite and syngenetic inclusions of columbite and Ta-Nb rutile. Muddy bluish-white beryl regenerated by colorless beryl from the Svetlinsky quarry hosts numerous syntactic inclusions of muscovite, gahnite, calcite, quartz and quartz-muscovite microaggregates with pyrite, chalcopyrite, sphalerite, galena, siderite, calcite, and micropores. The syntaxy of mica, quartz and gahnite with beryl is revealed for the first time.